2016
DOI: 10.3390/molecules21050548
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Biochanin A against β-Amyloid-Induced Neurotoxicity in PC12 Cells via a Mitochondrial-Dependent Apoptosis Pathway

Abstract: Abstract:Alzheimer's disease is considered one of the major neurodegenerative diseases and is characterized by the production of β-amyloid (Aβ) proteins and progressive loss of neurons. Biochanin A, a phytoestrogen compound found mainly in Trifolium pratense, was used in the present study as a potential alternative to estrogen replacement therapy via the investigation of its neuroprotective effects against Aβ 25-35 -induced toxicity, as well as of its potential mechanisms of action in PC12 cells. Exposure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…BA and Rh 2 both show no cytotoxicity at doses of 10–100 µM (data not shown). These data is supported by previous work performed by Tan and Kim reporting that 100 μM BA had no toxic effects in PC12 cells [ 18 ]. Furthermore, Quan’s studies have shown that Rh 2 at 80 µM dose exhibited no cytotoxic activity in the cells [ 19 ].…”
Section: Resultssupporting
confidence: 90%
“…BA and Rh 2 both show no cytotoxicity at doses of 10–100 µM (data not shown). These data is supported by previous work performed by Tan and Kim reporting that 100 μM BA had no toxic effects in PC12 cells [ 18 ]. Furthermore, Quan’s studies have shown that Rh 2 at 80 µM dose exhibited no cytotoxic activity in the cells [ 19 ].…”
Section: Resultssupporting
confidence: 90%
“…Biochanin A is an isoflavone with estrogenic activity in humans and has been identified in C. vulgaris [ 155 ]. Biochanin A exhibits neuroprotective activity against Aβ-induced neurotoxicity in PC-12 cells [ 156 ]. Furthermore, some carotenoids also protect the neurons against β-amyloid-induced neurotoxicity.…”
Section: Neuroprotective Potentials Of Microalgae Against Alzheimementioning
confidence: 99%
“…Over the past few years, the research on the isoflavones has mostly been focused on genistein, and the limited number of studies have been performed on the role of biochanin A. Interestingly, in our ongoing research of exploring natural BACE1 inhibitor, biochanin A exhibited significant BACE1 suppressing property compared with the other isoflavones including genistein. Furthermore, previous studies regarding on biochanin A displayed marked neuroprotective properties [14,15,16,17]. Biochanin A attenuated Aβ 25–35 -induced PC12 cell injury and apoptosis via preventing mitochondrial dysfunction [14].…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, previous studies regarding on biochanin A displayed marked neuroprotective properties [14,15,16,17]. Biochanin A attenuated Aβ 25–35 -induced PC12 cell injury and apoptosis via preventing mitochondrial dysfunction [14]. The compound protected dopaminergic neurons against LPS-induced damage through inhibition of microglia activation and production of proinflammatory factors [15].…”
Section: Introductionmentioning
confidence: 99%